Measurements of ion current from a corona-needle using a faraday cup electrometer - Panich Intra (2018)
Corona-needle charger is widely used to impose a known net charge distribution on the aerosol particles for the electrical mobility particle sizer. However, the corona discharge and charging processes in the corona-needle charger at different operating conditions is not well understood. In the present paper, measurement of ion current from a corona-needle charger using a Faraday cup electrometer was performed in order to optimize the coronaneedle charger with respect to maximization of the ion number concentration. It was shown that the corona onset increased with increasing air flow rate. At higher air flow rate, the ion current and concentration were found to be relatively high for the same corona voltage. The highest ion current in the Faraday cup electrometer was found to be about 6.4 × 10-10, and 6.29 × 10-10 A, corresponding to the ion number concentration of about 2.98 × 1013, and 2.93 × 1013 ions/m 3 occurring at the corona voltage of 2.9 and 3.7 kV for positive and negative coronas, and air flow rate at 8.0 L/min, respectively.